การประเมินมูลค่าทัศนียภาพของชายหาดหัวหินโดยแบบจำลองราคาแบบฮีดอนนิค: Economic Valuation of Hua Hin Beach Scenery by Hedonic Pricing Model - สิริโรจนพุฒิ วิไลวรรณ (Journal of Applied Economics and Management Strategy, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาคุณลักษณะที่มีผลต่อราคาคอนโดมิเนียม และประเมินมูลค่าทัศนียภาพของชายหาดหัวหิน จากราคาคอนโดมิเนียมบริเวณชายหาดหัวหิน อำเภอหัวหิน จังหวัดประจวบคีรีขันธ์ โดยใช้แบบจำลองราคาแบบฮีดอนนิค โดยใช้ข้อมูลราคาและคุณลักษณะของห้องคอนโดมิเนียมจำนวน 8 คุณลักษณะ จาก 127 ตัวอย่าง เก็บข้อมูลจากเว็บไซต์เกี่ยวกับคอนโดมิเนียม และสำนักงานขายในช่วงวันที่ 15 มกราคม - 15 กุมภาพันธ์ 2558 ผลการวิจัยพบว่า หากพื้นที่ทั้งหมดของโครงการคอนโดมิเนียมเพิ่มขึ้น 1 ตารางวา (4 ตารางเมตร) จะทำให้ราคาคอนโดมิเนียมเพิ่มขึ้น ร้อยละ 0.004 หากพื้นที่ของห้องคอนโดมิเนียมเพิ่มขึ้น 1 ตารางเมตร จะทำให้ราคาคอนโดมีเนียมเพิ่มขึ้นร้อยละ 1.21 และหากจำนวนห้องนอนเพิ่มขึ้น 1 ห้อง จะทำให้ราคาคอนโดมิเนียมเพิ่มขึ้นร้อยละ 23.49 นอกจากนี้ ราคาคอนโดมิเนียมของห้องที่อยู่ในตำแหน่งที่สามารถมองเห็นวิวทะเล มีการตกแต่งเฟอร์นิเจอร์ และอยู่ในตำแหน่งห้องมุม จะมีราคาแพงกว่าห้องที่ไม่มีคุณลักษณะดังกล่าว ค่าสัมประสิทธิ์ของตัวแปรวิวทะเลที่ประมาณการได้นำไปประเมินมูลค่าทัศนียภาพของชายหาดหัวหิน พบว่ามูลค่าทัศนียภาพของชายหาดหัวหิน เท่ากับ 530,431 บาท ถ้าหากราคาเฉลี่ยคอนโดมิเนียมบริเวณชายหาดหัวหิน เท่ากับ 4,851,032 บาท This study aims to 1) explore marketing environment of rubberwood sawn timber industry 2) study technical aspects of rubberwood sawn timber factory processing plant in Changwat Buri Ram 3) perform financial feasibility and 4) test the ability to sustain changes of rubberwood sawn timber factory plant in Changwat Buri Ram. The study uses primary data obtained from participatory observation and in-depth interviews and secondary data obtained from academic papers of various sources including the internet. Both types of data are used in descriptive and quantitative analyses. Financial tools are weighted average cost of capital (WACC), net present value (NPV), profitability index (PI), internal rate of return (IRR), modified IRR (MIRR), and switching value test (SVT). The study result shows that in 2014 Thailand have 54 rubberwood sawn timber factories producing 3 million m3 of rubberwood which is insufficient to meet demand of 8 million m3. Furthermore, Changwat Buri Ram does not yet have rubberwood sawn timber factory. Presently, there are rubber tree plantation for over 1,400 acres in Changwat Buri Ram which can be utilized as timbers in order to increase the product value. The estimated production capacity is 10,200 m3 per year. The factory plant required area of 10 rais and production technology of factory by using the Band Mill saw followed by Chemical Treatment and Vacuum Pressure Impregnation Process and the final process is drying in the stove in order to get rid of humidity. The financial result under project life of 10 years In case with BOI and Non-BOI WACC as discounted rate of 10.74 and 10.61 percent, the project is feasible for the investment since NPVs are calculated to be 18,528,388 and 30,106,403 Baht; PI are 1.35 and 1.57; IRR are 17.01 and 20.45 percent, and MIRR are 14.13 and 15.73 percent. The project risk is quite low.